Physiological-induced conductive response evaluation in specific muscle compartments under hybrid of electrical muscle stimulation and voluntary resistance training by electrical impedance tomography - Sun, Bo; Darma, Panji Nursetia; Sejati, Prima Asmara; Shirai, Tomoyuki; Narita, Kosei; Takei, Masahiro (Frontiers in Physiology, 2023)
Objective: The physiological-induced conductive response has been visualised for evaluation in specific muscle compartments under hybrid (hybridEMS) of electrical muscle stimulation (EMS) and voluntary resistance training (VRT) by electrical impedance tomography (EIT).Methods: In the experiments, tendency of conductivity distribution images σ over time was clearly detected for three specific muscle compartments, which are called AM1 compartment composed of biceps brachii muscle, AM2 compartment composed of triceps brachii muscle, and AM3 compartment composed of brachialis muscle, under three training modalities. Results: From the experimental results, the tendency of physiological-induced conductive response are increased in all three training modalities with increasing training time. Correspondingly, the spatialmean conductivity <σ>AM1,AM2,AM3 increased with the conductance value G and extracellular water ratio β of right arm by bio-impedance analysis (BIA) method. In addition, hybridEMS has the greatest effect on physiological-induced conductive response in AM1, AM2, and AM3. Under hybridEMS, the spatialmean conductivity increased from <σ pre >AM1 = 0.154 to <σ 23mins >AM1 = 0.810 in AM1 muscle compartment (n = 8, p < 0.001); <σ pre >AM2 = 0.040 to <σ 23mins >AM2 = 0.254 in AM2 muscle compartment (n = 8, p < 0.05); <σ pre >AM3 = 0.078 to <σ 23mins >AM3 = 0.497 in AM3 muscle compartment (n = 8, p < 0.05). This is a provisional file, not the final typeset articleThe paired-samples t-test results of <σ>AM1,AM2,AM3 under all three training modalities suggest hybridEMS has the most efficient elicitation on physiological induced conductive response compared to VRT and EMS. The effect of EMS on deep muscle compartment (AM3) is slower compared to VRT and hybridEMS, with a significant difference after 15 minutes of training.